Ijtihad: A Reflection On Its Role And Scope - Ali, Mohd Mumtaz (Journal of Islam in Asia (E-ISSN 2289-8077), 2012)
It is generally claimed that some of the outstanding features ofmodern age are the ‘rule of law’ and the emergence of ‘civil society’. In spite of supposedly civil and caring societies,millions of people around the world are still suffering from diseases, crimes and injustice. Onthe globalpolitical scene, ";;;might is right";;; prevails; more weapons arebeing produced thanrice and wheat. Sense of insecurity and violence is dominating everywhere. To overcome thisphenomenon, some analysts are suggesting a need for strong link between law and socialobligations, and some others are emphasizing the need to integrate moral and ethical valuesinto the sociopolitical sphere of our lives.However, our contention is that all these measures have proven superficial. The predicamentof modern societies cannot be alleviatedunless and until a strong relationship in between law,socialobligations and ijtihadis established and practiced in all spears of life. In this paper, it is argued that the real cause ofcontemporary malaise lies in the absence of ijtihad. Ijtihadis either neglected or restricted tocertain legal dimensions. This paper contends that only the application ofijtihad as the main methodology of thought and action would enhance consciousness of social obligations ofindividuals,policy makers, scientists, and political authorities, and would guarantee realcivilizational development. Hence, ijtihadshouldbe taken as the methodology ofdevelopment and civilization.